A comparative study of three validities computation methods for multimodel approach - Samia Talmoudi Ben Aoun; Abdennacer Ben Messaoud; Moufida Lahmari Ksouri (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The multimodel approach offers a very satisfactory results in modelling, diagnose and control of complex systems. In the modelling case, this approach passes by three steps: the determination of the model’s library, the validities computation and the establishment of the final model. In this context, this paper focuses on the elaboration of a comparative study between three recent methods of validities computation. Thus, it highlight the method that offers the best performances in term of precision. To achieve this goal, we apply, these three methods on two simulation examples in order to compare their performances.